Peran Orang Tua dalam Mendidik Akhlak Remaja di Masyarakat Sekeloa Tengah - Sabrina Arfa Andani; Dedih Surana (UNISBA Press, 2024)
Abstract The role of parents in educating adolescent morals is an important foundation for the development of character and morals of the younger generation. In Sekeloa Tengah, the challenges of daily life require parents to be more active and creative in educating their children. This study aims to: 1) determine parents' efforts in fostering adolescents at home; 2) describe parents' strategies in shaping adolescents' morals; and 3) identify supporting and inhibiting factors in the cultivation of morals by parents. This research uses a qualitative approach with observation, interview, and documentation methods. Data were analyzed through reduction, presentation, and conclusion drawing. The results showed that: 1) educating adolescent morals requires open communication and emotional support that makes children feel valued and confident, and fosters responsibility and discipline; 2) parents who use a holistic approach combine role modeling, open dialogue, and positive reinforcement to instill moral values; and 3) family, social environment, and school have a significant role in shaping adolescent morals. Abstrak Peran orang tua dalam mendidik akhlak remaja menjadi fondasi penting bagi perkembangan karakter dan moral generasi muda. Di Sekeloa Tengah, tantangan kehidupan sehari-hari menuntut orang tua untuk semakin aktif dan kreatif dalam mendidik anak-anak mereka. Penelitian ini bertujuan untuk: 1) mengetahui upaya orang tua dalam membina remaja di rumah; 2) mendeskripsikan strategi orang tua dalam membentuk akhlak remaja; dan 3) mengidentifikasi faktor pendukung serta penghambat dalam penanaman akhlak oleh orang tua. Penelitian ini menggunakan pendekatan kualitatif dengan metode observasi, wawancara, dan dokumentasi. Data dianalisis melalui reduksi, penyajian, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa: 1) mendidik akhlak remaja membutuhkan komunikasi terbuka dan dukungan emosional yang membuat anak merasa dihargai dan percaya diri, serta menumbuhkan tanggung jawab dan disiplin; 2) orang tua yang menggunakan pendekatan holistik menggabungkan keteladanan, dialog terbuka, dan penguatan positif untuk menanamkan nilai moral; dan 3) keluarga, lingkungan sosial, dan sekolah memiliki peran signifikan dalam pembentukan akhlak remaja.